14-3-3 and Smad2/3 are crucial mediators of atypical-PKCs: Implications for neuroblastoma progression - Breedy, S.; Ratnayake, W.S.; Lajmi, L.; Hill, R.; Acevedo-Duncan, M. (Frontiers in Oncology, 2023)
Neuroblastoma (NB) is a cancer that develops in the neuroblasts. It is the most common cancer in children under the age of 1 year, accounting for approximately 6% of all cancers. The prognosis of NB is linked to both age and degree of cell differentiation. This results in a range of survival rates for patients, with outcomes ranging from recurrence and mortality to high survival rates and tumor regression. Our previous work indicated that PKC-ι promotes cell proliferation in NB cells through the PKC-ι/Cdk7/Cdk2 cascade. We report on two atypical protein kinase inhibitors as potential therapeutic candidates against BE(2)-C and BE(2)-M17 cells: a PKC-ι-specific 5-amino-1-2,3-dihydroxy-4-(methylcyclopentyl)-1H-imidazole-4-carboxamide and a PKC-ζ specific 8-hydroxy-1,3,6-naphthalenetrisulfonic acid. Both compounds induced apoptosis and retarded the epithelial-mesenchymal transition (EMT) of NB cells. Proteins 14-3-3 and Smad2/3 acted as central regulators of aPKC-driven progression in BE(2)-C and BE(2)-M17 cells in relation to the Akt1/NF-κB and TGF-β pathways. Data indicates that aPKCs upregulate Akt1/NF-κB and TGF-β pathways in NB cells through an association with 14-3-3 and Smad2/3 that can be diminished by aPKC inhibitors. In summary, both inhibitors appear to be promising potential neuroblastoma therapeutics and merit further research.